Reformasi TNI: Pola, Profesionalitas, dan Refungsionalisasi Militer dalam Masyarakat - Basuki, Ahmad Yani (UI Scholars Hub, 2014)
As a process of military withdrawal from politics, the internal reform of The Indonesian National Defense Forces (Tentara Nasional Indonesia/TNI) has specific characters in its pattern as well as in its professionality. In this paper, Talukder Maniruzzaman’s concept of military withdrawal from politics and Robert K. Merton’s and Talcott Parsons’ functional analysis were laboured to inquire that process experienced by TNI. That inquiry used the combination of quantitative and qualitative methods. The result shows that TNI reform is a gradual, hierarchical and sustainable process. TNI reform can also categorized as professional military withdrawal from politics—a process which is not going suddenly nor hastily, with reformist considerations beforehand, and is based on an awareness about a need to correct TNI’s role in the past state politics. What makes it different from other countries’ military’s experiences is that this process had no immediate relationship to foregone general election, and were going without transfer of power to temporary civil government, social revolution, mass rebellion, or foreign invasion and intervention. Simultaneous with that reform is a process of refunctionalization, that is to say correctly reorder TNI’s position and role in the democratic order of national life, so TNI able to be functional simultaneously with other national functions or components.